PENGGUNAAN BERBAGAI CUT-OFF INDEKS MASSA TUBUH SEBAGAI INDIKATOR OBESITAS TERKAIT PENYAKIT DEGENERATIF DI INDONESIA - Heryudarini Harahap; Yekti Widodo; Sri Mulyati (GIZI INDONESIA, 2005)
DETERMINING CUT-OFF POINTS OF BODY MASS INDEX FOR OBESITY ASSOCIATED WITH DEGENERATIVE DISEASES IN INDONESIAObesity now is recognized as a public health problem. Changing diets and decreasing physical activity explain the increasing prevalence of obesity. Method that is commonly used for indentifying obesity is Body Mass Index (BMI). At present, there has been a growing debate on different BMI cut-off points for different ethnic groups, in particular for Asian population. A different cut-off point is needed due to evidence associated with BMI, percentage of body fat, and body fat distribution that differ across population. Therefore, health risks may incrase even below the cutoff point of 25 kg/m2 that now categorized as overweight. The objective of the study was to determine BMI cut-off points and their relationship with degenerative diseases. Data was originally taken from Health National Household Health Survei (SKRT) in 2004. The population were those who were aged 25 to 65 years old. The variable analysed statistically were age, sex, blood pressure, total cholesterol, and Diabetes Mellitus (DM). The analysis used in this study was univariate and bivariate tables to answer the objective. Based on WHO cut-off point, obesity was in BMI =25 kg/m2, and the prevalence of being hypertension, DM and hyperkolestrolemia as risks were 52.3%, 12,7% and 1,6% respectively. However, based on International Obesity Task Force (IOTF) cut-off in which pre obesity was started on BMI 23 kg/m2, the prevalence of each risk was consecutively 40,1%; 11,4% and 0,6%. Respectively cut-off used by Ministry of Health in obesity was 25 kg/m2 with prevalence for each risk was 50.2%, 11.8% and 1.5% respectively. Sensitivity (Se) and Specificity (Sp) were around 22.0-23.0 for all subjects based on sex, age, and education. The highest Se and Sp was found on hypercholesterol. Logistic regresion analysis showed that the increasing of BMI cut-off of 23 to 25 would be followed by the increase of the risk of hypercholesterol up to 0.6 points. On the other hand, decreasing BMI from 25 to 25 in USA may reduce 13% co-morbidity disease associated to obesity. In conclusion this study showed that on BMI =23.5 was related to degenerative diseases. However, the cut-off point still need to be examined in relation to the incidence of degenative diseases.Key Word: body mass index, cut-off point, degenerative diseases